Glycoengineered hepatitis B virus-like particles with enhanced immunogenicity. Issue 22 (8th May 2020) - Joe, Carina C.D.; Chatterjee, Sayantani; Lovrecz, George; Adams, Timothy E.; Thaysen-Andersen, Morten; Walsh, Renae; Locarnini, Stephen A.; Smooker, Peter; Netter, Hans J.
Abstract: Virus-like particles (VLP) represent biological platforms for the development of novel products such as vaccines and delivery platforms for foreign antigenic sequences. VLPs composed of the small surface antigen (HBsAgS) derived from the hepatitis B virus (HBV) are the immunogenic components of a licensed, preventative vaccine, which contains aluminum hydroxide as adjuvant. Herein, we report that glycoengineering of N -glycosylated HBsAgS to generate hyper-glycosylated VLPs display an enhanced immunogenicity relative to the wild type (WT) HBsAgS VLPs when expressed in FreeStyle HEK 293F cells. Comparative mass spectrometry-based N -glycan profiling, gel electrophoresis, and immunoassays demonstrated that WT and hyper-glycosylated HBsAgS VLPs contain the same type and distribution of N -glycan structures, but the latter shows a higher glycan abundance per protein mass. The antigenic integrity of the modified VLPs was also shown to be retained. To assess whether hyper-glycosylated VLPs induce an enhanced immune response in the presence of the adjuvant aluminum hydroxide, the anti-HBV surface antigen (anti-HBsAgS) antibody response was monitored in BALB/c mice, subcutaneously injected with different VLP derivatives. In the absence and presence of adjuvant, hyper-glycosylated VLPs showed an enhanced immunogenicity compared to WT VLPs. The ability of hyper-glycosylated VLPs to promote potent anti-HBsAgS immune responses compared to VLPs with a native N -glycan level as well as non-glycosylated, yeast-derived HBsAgS VLPs opens exciting avenues for generating more efficacious VLP-based vaccines against hepatitis B and improved HBsAgS VLP carrier platforms using glycoengineering.